Near stall unsteady flow responses to morphing flap deflections - Abdessemed, Chawki; Yao, Yufeng; Bouferrouk, Abdessalem (MDPI, 2021)
The unsteady flow characteristics and responses of an NACA 0012 airfoil fitted with a bio-inspired morphing trailing edge flap (TEF) at near-stall angles of attack (AoA) undergoing downward deflections are investigated at a Reynolds number of 0.62 × 106 near stall. An unsteady geometric parametrization and a dynamic meshing scheme are used to drive the morphing motion. The objective is to determine the susceptibility of near-stall flow to a morphing actuation and the viability of rapid downward flap deflection as a control mechanism, including its effect on transient forces and flow field unsteadiness. The dynamic flow responses to downward deflections are studied for a range of morphing frequencies (at a fixed large amplitude), using a high-fidelity, hybrid RANS-LES model. The time histories of the lift and drag coefficient responses exhibit a proportional relationship between the morphing frequency and the slope of response at which these quantities evolve. Interestingly, an overshoot in the drag coefficient is captured, even in quasi-static conditions, however this is not seen in the lift coefficient. Qualitative analysis confirms that an airfoil in near stall conditions is receptive to morphing TEF deflections, and that some similarities triggering the stall exist between downward morphing TEFs and rapid ramp-up type pitching motions.
Keywords: morphing; bioinspiration; dynamic mesh; RANS-LES; stress-blended eddy simulation (SBES); computational fluid dynamics (CFD); aerodynamics; stall; turbulent boundary layer